Effect of maturity stage on phenolic, flavonoid content, and antioxidant activity of cherry (Muntingia calabura) leaves extract - Yoyanda Bait; Yustinus Marsono; Umar Santoso; Djagal W. Marseno (Jurnal Agercolere, 2022)
The present work aims to investigate the maturation-related changes in phenolic, and flavonoid profiles, also the antioxidant activity of Muntingia calabura at two maturity stages (young and old leaves). The leaves were extracted using water as the solvent. The total phenol and flavonoid content were determined, and the antioxidant capacity using a spectrometry assay to determine antioxidant compounds in Muntingia calabura leaves. The extract was analyzed with Fourier-transform infrared spectroscopy (FTIR) and Liquid chromatography-mass spectrometry (LC-MS). The extracts of old leaves demonstrated a higher total phenolic content (160.00 mg GAE.g extract–1) and total flavonoid content (82.55 mg Quercetin.g extract–1) also exhibited stronger scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) 75.03% compared to young leaves. Based on the FTIR measurement of the young and old cherry leaves, shows a similar pattern in both stages of leaf maturity. On the other hand, the LC-MS test revealed 12 active components of the extract of cherry leaves.